A framework for unlocking large-scale urban regeneration projects - Schuchmann, Roberta (Curtin University, 2018)
This thesis investigates three large-scale urban projects in Australia: Kogarah in NSW, Dandenong in Victoria and Canning in Western Australia. Each is a regeneration site based upon transit-oriented development (TOD) principles. The findings of this research culminated in the creation of a framework that can be used for other regeneration projects, such as the Canning City Centre, a TOD in the planning phase.